2018
DOI: 10.1016/j.physa.2018.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties and multifractality of Bitcoin

Abstract: Using 1-min returns of Bitcoin prices, we investigate statistical properties and multifractality of a Bitcoin time series. We find that the 1-min return distribution is fat-tailed, and kurtosis largely deviates from the Gaussian expectation. Although for large sampling periods, kurtosis is anticipated to approach the Gaussian expectation, we find that convergence to that is very slow. Skewness is found to be negative at time scales shorter than one day and becomes consistent with zero at time scales longer tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 53 publications
6
66
1
Order By: Relevance
“…The Hurst exponent h(2) is estimated to be 0.144. This value is similar to those obtained for other assets(Gatheral , 2018;Bennedsen et al, 2016;Livieri et al, 2018). Table 1…”
Section: Resultssupporting
confidence: 88%
“…The Hurst exponent h(2) is estimated to be 0.144. This value is similar to those obtained for other assets(Gatheral , 2018;Bennedsen et al, 2016;Livieri et al, 2018). Table 1…”
Section: Resultssupporting
confidence: 88%
“…Based on the efficiency index, Kristoufek (2018) finds strong evidence that the Bitcoin markets remained mostly inefficient between 2010 and 2017. By analyzing one-minute returns from 2014 to 2016, Takaishi (2018) finds anti-persistence for high-frequency Bitcoin time series. Sensoy (2018) and Zargar and Kumar (2019) also report inefficiency of Bitcoin for high-frequency returns.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we calculate the generalized Hurst exponent, which characterizes the multifractal nature of the time series. The multifractality or generalized Hurst exponent of Bitcoin has also been addressed in the literature (Takaishi, 2018;Jiang et al, 2018;Al-Yahyaee et al, 2018;El Alaoui et al, 2018). Since Gaussian random time series show no multifractality, it has been suggested that the multifractal degree may be related to the degree to which a time series deviates from efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature on the cryptocurrency market is quite limited in the context of nonlinear behaviors of these instruments. The recent studies which discuss the chaotic dynamics of cryptocurrencies can be summarized as follows: Takaishi [33] and Lahmiri and Bekiros [34] independently studied the multifractality properties of bitcoin. Urquhart [35] studied the market inefficiency of bitcoin via random walks, whereas Bariviera [36] revisited the same topic by using Hurst exponent.…”
Section: Literature Reviewmentioning
confidence: 99%